GIS Visualisations of Mortuary Data from Holešov, Czech Republic - Ladislav Šmejda (Internet Archaeology, 2014)
This article presents a case-study demonstrating the potential of GIS visualisations for analyses of mortuary data, recorded half a century ago at the site of Holešov, Kroměříž district, in the Czech Republic. This cemetery consists of 10 Bell Beaker and 420 Early Bronze Age graves, giving the impression of continuous development over a considerable period of time. The temporality of the cemetery is examined in detail, via its chronological development, as well as the inseparable aspects of its social use and structuring through time.